2008
DOI: 10.1002/jbm.a.32177
|View full text |Cite
|
Sign up to set email alerts
|

Ag‐doped manganite nanoparticles: New materials for temperature‐controlled medical hyperthermia

Abstract: The purpose of this study was to introduce newly synthesized nanomaterials as an alternative to superparamagnetic ironoxide based particles (SPIO) and thus to launch a new platform for highly controllable hyperthermia cancer therapy and imaging. The new material that forms the basis for this article is lanthanum manganite particles with silver ions inserted into the perovskite lattice: La(1-x)Ag(x)MnO(3+delta). Adjusting the silver doping level, it is possible to control the Curie temperature (T(c)) in the hyp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(17 citation statements)
references
References 31 publications
0
16
0
1
Order By: Relevance
“…For example, fluorescent quantum dots [68], silver and zinc nanoparticles and lanthanum manganite particles with impregnated silver ions [69] have been explored. However, the general principles discussed for the three nanoparticles hold true in most cases.…”
Section: Hyperthermia With Cntsmentioning
confidence: 99%
“…For example, fluorescent quantum dots [68], silver and zinc nanoparticles and lanthanum manganite particles with impregnated silver ions [69] have been explored. However, the general principles discussed for the three nanoparticles hold true in most cases.…”
Section: Hyperthermia With Cntsmentioning
confidence: 99%
“…Jeyaraj et al [115] have shown that biogenic Ag NPs achieved by using Sesbania grandiflora leaf extract as a novel reducing agent have a cytotoxic effect against human breast cancer (MCF-7) cell lines. Ag NPs combined with lanthanum magnetite particles are also an ideal tool for inducing hyperthermia (TC 41-44 °C) [116]. Using starch-coated silver NPs have shown an antimitotic effect on human glioblastoma cells (U2510) and human lung fibroblast cells (IMR-90).…”
Section: Silver Nanoparticlesmentioning
confidence: 99%
“…To increase the absorption of NIR light and enhance the particle's functionality, magnetic nanocrystals can be synthesized with various coatings and ligands, such as gold 147149 , silica 150 , carbon nanotubes 151 , polymers 94,146,152 , TiO 2 153 , Ag 148,154 , graphitic carbon 29,94 , and upconversion crystals 155159 . The surface of magnetic particles can also be modified to be porous.…”
Section: Introductionmentioning
confidence: 99%